Kepuasan Orang Tua terhadap Kualitas Pelayanan Keperawatan pada Pasien Anak di RSIA Sitti Khadijah Gorontalo - Botutihe, Abd Hafit; Modjo, Dewi; Asnawati, Rini; Ali, Lenny (Pustaka Galeri Mandiri, 2026)
Nursing services are professional healthcare services provided by nurses to meet the health needs of individuals, families, groups, and communities comprehensively. The quality of nursing services plays an important role in determining patient and family satisfaction, particularly in pediatric care settings where parents are actively involved in the treatment process. This study aimed to describe the level of parental satisfaction with nursing services in the pediatric ward of RSIA Sitti Khadijah Gorontalo. This study employed a quantitative descriptive design. The population consisted of 288 parents of pediatric patients, while 75 respondents were selected using the Slovin formula. Data were collected using a questionnaire based on five dimensions of nursing service quality, namely reliability, responsiveness, assurance, empathy, and tangibles. Data were analyzed using univariate analysis and presented in frequency distributions. The results showed that the reliability dimension was categorized as good by 92.0% of respondents, responsiveness by 90.7%, assurance by 89.3%, empathy by 90.7%, and tangibles by 92.0%. Overall, parental satisfaction in the pediatric ward of RSIA Sitti Khadijah Gorontalo was predominantly categorized as satisfied, with 74.6% of respondents reporting satisfaction. These findings indicate that nursing services provided in the pediatric ward have met parental expectations. Continuous quality improvement is needed to maintain and enhance parental satisfaction with nursing care services.